Active citizenship in context - Spajić-Vrkaš, Vedrana (2009)
Whether, how, and how efficiently the students are prepared for active citizenship depends, to a great extent, on the nature of learning environment known as school culture, climate or ethos. While one school may easily adapt to the needs of promoting students’ participation as a means of learning active citizenship, the other may divert or hinder such change. In order to explore and understand how different school settings work and what strategies should be applied in each of them, the participants will engage in two scenarios depicting two opposing school culture - authoritarian vs. liberal-individualistic. Through group-work they will be asked to develop strategic plans for enhancing students’ participation on the basis of the so-called ‘progression chart’ that has recently been developed by the Council of Europe.